Pengaruh Total Asset Turnover Dan Return On Asset Terhadap Harga Saham Pada PT Kabelindo Murni Tbk - Furkan (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to determine the effect of total asset turnover, return on assets on stock prices. The population in this study was 31 years and the sample was 10 years. The statistical tool uses SPSS with the classic assumption test, t test and F test. The results in this research partially total asset turnover, return on assets have an influence on stock prices while simultaneously they influence stock prices.